Pengaruh Fatherless terhadap Kepercayaan Diri Remaja SMA Negeri Wolwal Kabupaten Alor Barat Daya - Mali, Samrin Hasan; Nalle, Andriani Paulin; Abel, Rizky Mayesita (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
Fatherless is the absence of a father figure in a child's life.. Fatherless also greatly affects the development of students such as the formation of self-confidence in the environment where they live. This study aims to determine: (1) Fatherless description of teenagers' self-confidence at Wolwal Senior High School in Southwest Alor, (2) Self-confidence description of teenagers at Wolwal Senior High School in Southwest Alor, (3) Fatherless influence on teenagers' self-confidence at Wolwal Senior High School in Southwest Alor. This research used quantitative approach with simple linear regression research type. This research was conducted on students of SMAN Wolwal Alor Barat Daya with a population of 187 students and a sample of 125 students. The sampling technique used is probability sampling technique with disproportionate stratified random sampling method, to determine the sample size used Slovin technique. The data collection technique used in this study was a questionnaire, namely a fatherless questionnaire (23) and a self-confidence questionnaire (33), with the scale used being a Likert scale. The data analysis technique used is descriptive analysis and simple linear regression analysis technique with the help of SPSS software version 25. The results of this study indicate that in general fatherless students are in the middle category, namely 87 students (70%), and the self-confidence of adolescents of SMA Negeri Wolwa, Southwest Alor Regency is also in the middle category, namely 102 students (82%). The results of the analysis showed Fcount of 20.590> Fubel 3.92 (N = 125) with a significance level of 0.000 <0.05, with a diterminasi coefficient (R Square) of 0.143, which implies that fatherless affects the self-confidence of adolescents at SMA Negeri Wolwal Southwest Alor by 14, 3%, and the remaining 85.7% is influenced by other factors such as self-control, self esteem, psychological well being, learning achievement and social adjustment.